In vitro mutagenesis and somaclonal variation in banana to increase drought tolerance - Shirani Bidabadi, Siamak (2011)
Banana production is threatened by several abiotic stresses, such as drought, thus, developing tolerant genotypes towards water stress is needed. Genetic variability in banana is narrow due to low female fertility, therefore, this study aimed to use somaclonal variation caused by ethyl methanesulphonate (EMS) to select drought tolerant mutants of banana. The first step in conducting in vitro mutagenesis experiments was to optimize an efficient micropropagation system because of significant loss of many new mutants due to the deficiency of a regeneration system after in vitro mutagenesis. Results indicated that the highest rates of proliferation associated with low percentage of abnormality ranging from ‘3.44 (8% abnormality)’, 4.22 (30% abnormality) and 7.67 (24% abnormality) occurred in ‘Berangan Intan’, ‘Berangan’ and ‘Rastali’, respectively on medium containing 22.2 μM BAP. Although proliferation rate was greater with TDZ than the other cytokinins, treatments with TDZ produced more abnormality, sometimes as high as 82%. Furthermore, using the RAPD markers, the somaclones regenerated by TDZ exhibited higher percentage of polymorphism than BAP. Consequently, supplementation of 22.2 μM BAP in MS medium was assumed the most suitable for commercial micropropagation system with low frequency of abnormal shoot production. Different ethyl methanesulphonate (EMS) treatments were applied to investigate their effects on proliferating shoot tips and to evaluate the potential of EMS to create variability among banana cultivars. The percentage of surviving shoot tips ranged from 88.71, 81.10 and 90.62 with 150 mM EMS for 30 min to 37.78, 34.44 and 31.03 with 250 mM EMS for 60 min in ‘Berangan Intan’, ‘Berangan’ and ‘Rastali’ respectively. The average number of shoots per explant declined significantly from the controls to the highest dose and duration of EMS. The recommended treatments were adjudged to be 60 min/200 mM and 30 min/250 mM of EMS for all cultivars tested in this study, which resulted in phenotypic variations of 10.74% and 9.65% respectively for ‘Berangan Intan’, 12.42% and 7.20% respectively for ‘Berangan’, 13.17% and 14.78% respectively for ‘Rastali. In vitro selection involving 14 EMS –induced mutant somaclones of banana through screening of shoot tips on media stressed with different levels of polyethylene glycol (10, 20 and 30 g L-1) based on morphological, physiological and molecular markers was attempted to develop drought-tolerant lines. Data recorded at each stress level, showed that mutants L2-5 and L1-5, followed by L2-4, L1-4 and then L1-3 and L2-6 demonstrating stronger tolerance against water stress, exhibited higher shoot vigour, fresh weight increase, proliferation rate, proline, relative water and chlorophyll content than the rest and control parental clones. In spite of the relatively large number of polymorphic bands found in the 14 clones of Musa cultivars ‘Berangan Intan’ and ‘Berangan’, only primers opc01, opa11, opa20 and opc04 generated bands that could be considered as potential markers to indentify drought resistant somaclones. The amplified fragments observed to be specific for the somaclones L2-5 and L1-5 as more drought tolerant and somaclones L2-3, L1-4, L2-6 and L1-6 as moderately drought tolerant could be markers for initial estimation and selection for water stress tolerance in banana cultivars.